AllerGAtlas 1.0: a human allergy-related genes database. (22nd February 2018) - Liu, Jinying; Liu, Yuan; Wang, Dan; He, Mengqi; Diao, Lihong; Liu, Zhongyang; Li, Yang; Tang, Li; He, Fuchu; Li, Dong; Guo, Shuzhen
Abstract: Allergy is a detrimental hypersensitive response to innocuous environmental antigen, which is caused by the effect of interaction between environmental factors and multiple genetic pre-disposition. In the past decades, hundreds of allergy-related genes have been identified to illustrate the epidemiology and pathogenesis of allergic diseases, which are associated with better endophenotype, novel biomarkers, early-life risk factors and individual differences in treatment responses. However, the information of all these allergy-related genes is dispersed in thousands of publications. Here, we present a manually curated human allergy-related gene database of AllerGAtlas, which contained 1195 well-annotated human allergy-related genes, determined by text-mining and manual curation. AllerGAtlas will be a valuable bioinformatics resource to search human allergy-related genes and explore their functions in allergy for experimental research. Database URL : http://biokb.ncpsb.org/AlleRGatlas/